Pengembangan Sistem Manajemen Kartu Rencana Studi (KRS) berbasis Web (Studi Kasus: Sekolah Tinggi Teologi Tawangmangu) - Jovita Nathania Tunliu; Tri Astoto Kurniawan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
The activity of writing a Course Selection Sheet (KRS) is one of the academic activities routinely carried out by the Sekolah Tinggi Teologi Tawangmangu. The purpose of writing KRS is to find out which students are active in the semester that will be implemented and what courses will be taken. In the implementation of KRS writing, Sekolah Tinggi Teologi Tawangmangu still uses the manual method, namely students write on the paper that has been provided and submit it to the academic. Manually writing KRS often causes problems such as delays in submitting KRS, damage to KRS sheets, unclear writing and or mistakes by academics in recapitulating data in Microsoft Excel applications. The web-based KRS management system is a solution to overcome problems in the implementation of KRS writing at Sekolah Tinggi Teologi Tawangmangu. System development is carried out using the Waterfall development model and object oriented approach. The system is built using PHP programming language with Codeigniter framework and MySQL as a database management system. The KRS management system was tested using unit testing, integration and validation strategies. Unit and integration testing is carried out using white-box testing techniques and validation testing is carried out using black box testing techniques. White-box testing was carried out on 6 sample methods and resulted valid status for all samples. Black-box testing was carried out on 28 functional systems and resulted valid status for all functionalities.